Instagram as a Communication Space for Painters - Garwol, Katarzyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
Instagram is a social network platform intended for communication between the creator of information and its recipients, as well as between the recipients themselves. The driving force of Instagram has been recognised by many artists that decided to promote their creative work on this platform. This social network is also used to fulfil advertising contracts that the artists have concluded with companies. The question therefore is whether the number of followers is mainly affected by the artistic achievements of their authors or by out-of-art marketing activities? Instagram contains many profiles of people involved in other branches of art, including painting. It seems that due to the field of art they deal with, the private life of an artist painting pictures is not as interesting as the life of popular actors or singers. As a result, their profiles are mainly concentrated on presenting artistic achievements using a platform that helps them reach a broad spectrum of viewers. This article provides a selective review of popular profiles of artists, taking into consideration the way in which they present their art on the Internet and how the artist communicates with users, as well as how the communication between users themselves looks.